Language and politics - Joseph, John Earl (Edinburgh : Edinburgh University Press, 2006)
Language, this book argues, is political from top to bottom, whether considered at the level of an individual speaker's choice of language or style of discourse with others (where interpersonal politics are performed), or at the level of political rhetoric, or indeed all the way up to the formation of national languages. By bringing together this set of topics and highlighting how they are interrelated, the book will function well as a textbook on any applied or sociolinguistic course in which some or all of these various aspects of the politics of language are covered. The chapter headings include: How politics permeates language (and vice-versa) Language and nation The social politics of language choice and linguistic correctness Politics embedded in language Taboo language and its restriction Rhetoric, propaganda and interpretation Power, hegemony and choices
Cover -- Contents -- Series Editors' Preface -- Foreword -- Chapter 1: Overview: How politics permeates language (and vice versa) -- 1.1 What does it mean to say that language is political? -- 1.2 The politics of different ways of speaking -- 1.3 The politics of talking to others -- 1.4 The politics of what 'the language' is -- 1.5 The politics of which language to speak -- 1.6 The politics of policing the language -- 1.7 Language, thought and politicians -- 1.8 Language and choice -- 1.9 Conclusion: Language is political from top to bottom -- Notes -- Chapter 2: Language and nation -- 2.1 Them and us -- 2.2 What is or isn't 'a language' -- 2.3 The role of writing -- 2.4 Constructing 'the language' by controlling variation -- 2.5 Language, knowledge and power -- 2.6 How new languages emerge: From 'falling standards' to 'World Englishes' -- 2.7 Oppression and identity -- Suggested further reading -- Notes -- Chapter 3: The social politics of language choice and linguistic correctness -- 3.1 Hearers as speakers -- 3.2 The denial of heteroglossia -- 3.3 The role of education -- 3.4 Linguistic imperialism -- 3.5 Language rights -- 3.6 The linguistic performance of minority identities -- Suggested further reading -- Notes -- Chapter 4: Politics embedded in language -- 4.1 Struggle in the sign -- 4.2 Struggle in interaction -- 4.3 Deferential address -- 4.4 Gendered language -- 4.5 'Powerless' language -- 4.6 The politics of language change -- Suggested further reading -- Notes -- Chapter 5: Taboo language and its restriction -- 5.1 Swearing -- 5.2 The language police state -- 5.3 The politics of (self- )censorship -- 5.4 Hate speech -- 5.5 The right to hear no evil? -- Suggested further reading -- Notes -- Chapter 6: Rhetoric, propaganda and interpretation -- 6.1 Rhetoric versus truth? -- 6.2 Language, thought and reality -- 6.3 Propaganda anxiety -- 6.4 Newspeak -- 6.5 Linguistic creativity and manufacturing consent -- 6.6 Critical Discourse Analysis -- 6.7 The function of language in a democracy -- Suggested further reading -- Notes -- Chapter 7: Conclusion: Power, hegemony and choices -- 7.1 Agency -- 7.2 Broccoli theory -- 7.3 Conclusions -- 7.4 Implications and applications -- References.
Includes bibliographical references (pages 150-162) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Language and languages -- Political aspects; Language policy; Langage et langues -- Aspect politique; REFERENCE; LANGUAGE ARTS & DISCIPLINES -- Vocabulary; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Language and languages -- Political aspects; Language policy; Sprache; Politik; Taalgebruik; Taalpolitiek; Langage et langues -- Aspect politique; Hommes politiques -- Langage et langues; Englisch; Electronic books; Electronic books